2021
DOI: 10.1101/2021.01.07.424493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commercial vaccines do not confer protection against two genetic strains ofPiscirickettsia salmonis, LF-89-like and EM-90-like, in Atlantic salmon

Abstract: In Atlantic salmon, vaccines have failed to control and prevent Piscirickettsiosis, for reasons that remain elusive. In this study, we report the efficacy of a commercial vaccine developed with the Piscirickettsia salmonis isolate AL100005 against other two isolates which are considered highly and ubiquitously prevalent in Chile: LF-89-like and EM-90-like. Two cohabitation trials were performed to mimic real-life conditions and vaccine performance: 1) post smolt fish were challenged with a single infection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…Thus ( 72 ), suggested that this strong local response could lead to an overestimation of vaccine efficacy if fish are IP-challenged a few weeks after vaccination. These results are consistent and explain very well the low efficacy of some experimental and commercial vaccines observed in cohabitation trials despite achieving high amounts of host IGM expression ( 61 , 110 113 ).…”
Section: Why Vaccines Fail Against Piscirickettsiosis?supporting
confidence: 83%
“…Thus ( 72 ), suggested that this strong local response could lead to an overestimation of vaccine efficacy if fish are IP-challenged a few weeks after vaccination. These results are consistent and explain very well the low efficacy of some experimental and commercial vaccines observed in cohabitation trials despite achieving high amounts of host IGM expression ( 61 , 110 113 ).…”
Section: Why Vaccines Fail Against Piscirickettsiosis?supporting
confidence: 83%